Degree Apprenticeships in England and the Recognition of Prior Learning: Democracy in Action? (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The number of mature students entering higher education (HE) as part-time learners has fallen dramatically in England since 2009 with equality and social mobility effects. The causes attributed include economic downturn and the 2012 higher education funding reforms which led to a substantial increase in tuition fees (Hubble &Bolton, 2022). One national policy initiative potentially addressing this decline is the introduction of Degree Apprenticeships. These programs uniquely integrate the development of knowledge, skills, and behaviors across work and undergraduate/postgraduate study with a core requirement for the Recognition of Prior Learning (RPL). Potentially, they offer a route to HE level qualifications for skilled migrants, individuals disadvantaged through barriers to accessing formal training and education, and those with the necessary skills and knowledge who are excluded from accessing career development opportunities because they lack a degree qualification. RPL in HE has traditionally been a marginal activity with most undergraduate recruitment targeted at school leavers. Drawing on research using actor-network-theory this paper examines the way in which RPL can be constructed as a vehicle for prior learning translation and transfer (Pokorny,2023) in a specific degree apprenticeship context empowering learners; accelerating their study time by up to 2/3rds and preparing them for success in HE, as demonstrated by their degree outcomes. It also considers whether the degree apprenticeship in England is indeed evidence of democracy in action.